2013
DOI: 10.1371/journal.pone.0057325
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in the Recognition of Facial Expressions: An Event-Related Potentials Study

Abstract: Previous studies have shown that early posterior components of event-related potentials (ERPs) are modulated by facial expressions. The goal of the current study was to investigate individual differences in the recognition of facial expressions by examining the relationship between ERP components and the discrimination of facial expressions. Pictures of 3 facial expressions (angry, happy, and neutral) were presented to 36 young adults during ERP recording. Participants were asked to respond with a button press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…Past studies have used the non-lateralized N170 as an electrophysiological measure of face encoding and assessed effects of facial expression (Batty and Taylor, 2003;Schyns et al, 2007;Leppanen et al, 2008;Righart and de Gelder, 2008;Smith et al, 2013;Turano et al, 2017). In this study, we did not find changes of the non-lateralized N170 as a function of facial expression, which is in line with previous studies (Pourtois et al, 2005;Rellecke et al, 2012;Calvo and Beltran, 2013;Tamamiya and Hiraki, 2013;Neath-Tavares and Itier, 2016; for review, see Hinojosa et al, 2015). In contrast to prior studies, however, task demands did not modulate the effect of facial expression on the non-lateralized N170 (Eimer et al, 2003;Holmes et al, 2003Holmes et al, , 2006Neath-Tavares and Itier, 2016; for review, see Eimer and Holmes, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Past studies have used the non-lateralized N170 as an electrophysiological measure of face encoding and assessed effects of facial expression (Batty and Taylor, 2003;Schyns et al, 2007;Leppanen et al, 2008;Righart and de Gelder, 2008;Smith et al, 2013;Turano et al, 2017). In this study, we did not find changes of the non-lateralized N170 as a function of facial expression, which is in line with previous studies (Pourtois et al, 2005;Rellecke et al, 2012;Calvo and Beltran, 2013;Tamamiya and Hiraki, 2013;Neath-Tavares and Itier, 2016; for review, see Hinojosa et al, 2015). In contrast to prior studies, however, task demands did not modulate the effect of facial expression on the non-lateralized N170 (Eimer et al, 2003;Holmes et al, 2003Holmes et al, , 2006Neath-Tavares and Itier, 2016; for review, see Eimer and Holmes, 2007).…”
Section: Discussionsupporting
confidence: 92%
“…Several studies have linked overall social and communication impairment to the ability to successfully identify others' emotions from their facial expressions (Knox and Douglas, 2009, McDonald and Flanagan, 2004, Pettersen, 1991, Watts and Douglas, 2006), suggesting that poor interpersonal skill might be attributed—at least partially—to deficits in emotion perception and interpretation. Emotion recognition abilities show marked individual differences both within healthy (Germine and Hooker, 2011, Palermo et al, 2013, Tamamiya and Hiraki, 2013) and brain injury populations (Babbage et al, 2011, Rigon et al, 2016b, Rosenberg et al, 2014). Indeed, among groups of individuals with TBI that would otherwise be defined as homogeneous (i.e., as “moderate”, “severe”, or “moderate-severe” (Malec et al, 2007)), great variability in facial-affect recognition skills has been reported (Rigon et al, 2016b, Rosenberg et al, 2014), leading to a considerable challenge for clinicians attempting to predict deficit profiles and long-term interpersonal outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, no significant effects were found in the N170. Given that the N170 reflects categorization of facial expressions (Tamamiya & Hiraki, 2013), playing a violent video game might not affect any sort of categorization process. According to Sharma and McKenna (2001), several studies, using both clinical and nonclinical samples, have demonstrated that emotionally laden stimuli that correspond to the emotional state of the participant produce greater interference (i.e., longer response latencies) than neutral stimuli.…”
Section: Discussionmentioning
confidence: 99%
“…N170 was measured at P7 and P8. P2 was measured at O1 and O2 (Latinus & Taylor, 2005;Tamamiya & Hiraki, 2013). Latencies were taken at the electrode where amplitude was maximal over each hemisphere, and amplitudes were measured at this latency.…”
Section: Electrophysiological Recording and Analysismentioning
confidence: 99%
See 1 more Smart Citation